Tingkat Stres Ibu Muda di Masa Pandemi Covid-19: Bagaimana Peran Resiliensi dan Sikap Sabar? - Medina Chodijah (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study aims to examine the role of resilience and patience on stress level experienced by young mothers during Covid-19 pandemic. This study is a quantitative correlational research using 3 instruments in a set of questionnaire that is: resilience and patience questionnaire developed by the researcher, and Pandemic-Related Perceived Stress Scale of Covid-19 (PRPSSC) developed by Campo-Arias and colleagues. The participants were 44 young mothers who have 1st- and 2nd-grader children in Pasirbitung village, Tasikmalaya. The results show that most of the participants have resilience (70.4%) and patience (88.6%) in high level, and stress in mild level (70.5%). Resilience and patience have negative effect on stress level of the mothers. That is, the higher resilience and patience, the lower stress experienced by the mothers.